Effects of saline irrigation water on morphological characteristics of banana (Musa spp.) - Al Harthy, Khalid Mubarak Saleh; Hassan, Siti Aishah; Awang, Yahya; Ismail, Roslan; Al-Yahyai, Rashid Abdullah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2018)
Banana is one of the most important food crops after rice, wheat and corn around the world. It is susceptible to a wide spectrum of non-infectious problems such as abiotic stresses resulting in restricting growth and production. Studies were conducted to determine the effects of four salinity levels (0.17 (control), 3.0, 6.0, and 9.0 dS m-1) on morphological characteristics of four banana cultivars at vegetative growth stage. Banana cultivars from the Cavendish group (Williams, Malindi) and plantains group (FHIA18 and Diwan) were grown in 61 x 76 cm polyethylene bags filled with soil mixture comprising of top soil, sand and peat moss (3:1:2 v/v), with pH ranging from 6 - 6.5 and EC 0.02 mScm-1. The experiment was carried out under a rain-shelter in split-plot design with three replicates. Plants were irrigated manually. Data were collected at 3, 6 and 9 months after transplanting. The results revealed that, the number of leaves, stem height, stem girth and total leaf area were significantly affected by salinity, variety and plant age. Significant interaction was also found between salinity and variety, salinity and plant age, as well as variety and plant age. The morphological characteristics of banana were negatively affected by higher salinity levels (6.0 and 9.0 dS m-1). Under similar salinity level, cultivar Malindi had higher number of leaves, stem height, stem girth and total leaf area as compared to cultivar Williams. Among plantains banana, cultivar FHIA18 was more tolerance to high salinity levels than Diwan cultivar, while Malindi from Cavendish group shows high salt tolerant than Williams. Therefore cultivars Malindi and FHIA18 could be grown in arid and semiarid environment depend on their tolerance to high salinity level above 1.0 dS m-1.